Circulating Tumor Cells in Cancer Diagnosis, Therapy, and Theranostics Applications: An Overview of Emerging Materials and Technologies - Soleymani, Sina; Naghib, Seyed Morteza; Mozafari, M.R. (Current Pharmaceutical Design, 2025)
In recent years, immunotherapy, namely immune checkpoint inhibitor therapy, has significantly transformed the approach to treating various forms of cancer. Simultaneously, the adoption of clinical oncology has been sluggish due to the exorbitant expense of therapy, the adverse effects experienced by patients, and the inconsistency in treatment response among individuals. As a reaction, individualized methods utilizing predictive biomarkers have arisen as novel strategies for categorizing patients to achieve successful immunotherapy. Recently, the identification and examination of circulating tumor cells (CTCs) have gained attention as predictive indicators for the treatment of cancer patients undergoing chemotherapy and for personalized targeted therapy. CTCs have been found to exhibit immunological checkpoints in several types of solid tumors, which has contributed to our understanding of managing cancer immunotherapy. Circulating tumor cells (CTCs) present in the bloodstream have a crucial function in the formation of metastases. Nevertheless, the practical usefulness of existing CTC tests is mostly restricted by methodological limitations.
Keywords: inhibitor therapy